Relationship between ITPA polymorphisms and hemolytic anemia in HCV-infected patients after ribavirin-based therapy: a meta-analysis - Pineda-Tenor, Daniel (J Transl Med, 2015)
BACKGROUND: There is growing evidence that variations in the gene encoding inosine triphosphate pyrophosphohydrolase (ITPase), known as inosine triphosphatase (ITPA), are related to hemolytic anemia, which is frequently observed among hepatitis C virus (HCV)-infected patients receiving ribavirin (RBV)-based therapy. We performed a meta-analysis of all eligible studies assessing ITPA gene polymorphisms related to RBV-induced hemolytic anemia in HCV-infected patients published in PubMed, Embase and the Cochrane library prior to the end of 2014. METHODS: Three outcomes were evaluated: (1) hemoglobin decline, (2) severe anemia, and (3) RBV dose reduction or treatment discontinuation. Pooled odds ratio (OR) and 95 % confidence interval (95 % CI) were estimated by either fixed or random effects models. RESULTS: Twenty-nine studies were selected from the literature search: 20 references involving 6533 individuals for hemoglobin decline, 13 references on 3764 patients for severe anemia, and 16 references on 3918 patients for RBV dose reduction or discontinuation. Significant associations with hemoglobin decline were found for rs1127354 CC [OR = 12.84 (95 % CI 7.44; 22.17)], rs7270101 AA [OR = 3.41 (95 % CI 2.08; 5.59)] and rs6051702 AA [OR = 4.43 (95 % CI 2.80; 7.00)] genotypes. Moreover, significant associations with hemoglobin decline were also found for absent [OR = 6.01 (95 % CI 4.84; 7.46)] and mild [OR = 4.68 (95 % CI 2.83; 7.74)] ITPase deficiency haplotypes. The ITPA rs1127354 CC genotype and absent ITPase deficiency haplotype were also associated with severe anemia {[OR = 7.77 (95 % CI 5.03; 12.00)] and [OR = 4.79 (95 % CI 1.69; 13.56)], respectively}. Additionally, the rs1127354 CC genotype showed significant association with RBV dose reduction or stopping treatment (OR = 2.24; 95 % CI 1.79; 2.81). CONCLUSIONS: ITPA polymorphisms increase the likelihood of developing hemolytic anemia for HCV-infected patients on RBV-based therapy, particularly rs1127354 CC and rs7270101 AA genotypes, suggesting the utility of screening for ITPA polymorphisms to avoid hematological toxicity and increase adherence to RBV-based therapy. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12967-015-0682-y) contains supplementary material, which is available to authorized users.